Income Inequality in Bolivia, Colombia, and Ecuador: Different Reasons - María Aristizábal-Ramírez; Gustavo J Canavire Bacarreza; Michael Jetter (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the individual-level determinants of wage inequality for Bolivia, Colombia, and Ecuador from 2001 to 2010. Using a rich annual data set from surveys in all three countries, we analyze wages both using conventional wage regressions and decompositions of standard Gini indices. Although popular opinion and standard Gini indices suggest Colombia to exhibit the most unequal distribution of income among these countries, our results suggest otherwise. If one assumes educational attainment to form part of one's own responsibility the Colombian income distribution appears more equal than Bolivia's or Ecuador's. In 2010, educational achievement explains over 10.9 percent of the Gini score in Colombia, 6.3 percent in Ecuador, and a mere 2.4 percent in Bolivia. Our findings show that the sources of income inequality can differ substantially across countries. Respective policy prescriptions should differ accordingly.
Keywords: D31; D63; J31; 330; income inequality; Gini coefficient; unfair inequality